Edmans, Alex. May Contain Lies: How Stories, Statistics, and Studies Exploit Our Biases—And What We Can Do about It - Golman, Russell; Saccardo, Silvia (Journal of Economic Literature, 2025)
Russell Golman of Carnegie Mellon University and Silvia Saccardo of Carnegie Mellon University review “May Contain Lies: How Stories, Statistics, and Studies Exploit Our Biases – And What We Can Do about It” by Alex Edmans. The Econlit abstract of this book begins: “Explores how one might separate myth from reality, providing a practical guide to help people think more critically about topics including how to run a company and invest money, what drives global warming and the spread of pandemics, and which policies lawmakers should pass and voters should support.”